JUAL BELI ONLINE DALAM PERSPEKTIF EKONOMI ISLAM PADA MAHASISWA FEBI UNZAH - Fajri, Ahmad (universitas Islam Zainul Hasan Genggong, 2023)
This study aims to examine the practice of online buying and selling conducted by students of the Faculty of Islamic Economics and Business at Zainul Hasan Islamic University (UNZAH), as well as to analyze these practices from the perspective of Islamic economics. The research employs a descriptive qualitative method with a case study approach. The data sources consist of both primary and secondary data, collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings indicate that online buying and selling practices among UNZAH students are carried out in two main stages. The first is the transaction mechanism stage, which begins with the buyer placing an order, followed by the online payment process. Several payment systems are utilized, including bank transfers, credit cards, PayPal, e-wallets, and Cash On Delivery (COD) systems. From the perspective of Islamic economics, the online buying and selling practices carried out by students generally comply with Islamic legal principles. These include requirements that the products sold must be halal and of good quality, the ownership status of the goods must be clear (whether they are personally owned or second-hand), and product quality must be guaranteed. Additionally, there should be a fair correlation between the price and quality of goods to prevent buyer dissatisfaction. Honesty in transactions must also be upheld, particularly concerning the level of trustworthiness between both parties involved.